Extreme heat vulnerability assessment in Peninsular Malaysia with integration of remote sensing and sociodemographic data - Ahmad Kamal, Nurfatin Izzati (2021)
The inevitable increase in temperature have attributed to the episodes of extreme heat all over the world and causes significant impacts on health, society, and economics. In the past 10 years, Malaysia has experienced more extreme heat event and yet very little research has been dedicated in exploring the heat-related vulnerability of exposed populations. In this study, the spatial and temporal pattern of extreme heat event was assessed, and the extreme heat vulnerability index (EHVI) has been evaluated based on integration of exposure, sensitivity and adaptive capacity during reference year and extreme heat year. The spatio-temporal distribution of extreme heat exposure was assessed using daytime land surface temperature (LST) Moderate Resolution Imaging Spectroradiometer (MODIS) Aqua Earth Observation satellite from 2003 until 2018. We have applied Principal Component Analysis on 13 parameters for each 87 districts to elucidate the extreme heat vulnerability in Peninsular Malaysia. The EHVI were generated by summing up the normalized extreme heat exposure scores and factors scores from the multivariate analysis. Comparison between reference year and extreme heat year was done to evaluate the change of extreme heat exposure and vulnerability between those years. Then, the relationship between EHVI and actual heat related illness was analysed using multinomial logistic regression. The result shows that there is significant increase of LST annually and during southwest monsoon. It was found that from 2003 until 2018, El-Nino accounts about 7.8% of extreme heat event and the highest LST anomaly is 3.2°C on March 2016. The analysis reveals two major components that represents the 13 parameters: social sensitivity and adaptive capacity. EHVI in our study clarifies that the most vulnerable populations are confined in the urban and northern region of Peninsular Malaysia. The source of vulnerability varied between both regions, with urbanization and population density increase the vulnerability in urban areas while high heat exposure and sensitive population are the dominant factor of vulnerability in northern region. The result also shows that EHVI is a significant predictor for district with moderate heat related cases. A comprehensive heat vulnerable assessment will give decision-makers, planner and other stakeholders, a clear view for effective adaptation and preparedness strategies in undergo future heat-related events.